Media Literacy and Technology Skills of Physical Education Students - Fika Ulandari; Andika Triansyah; Fitriana Puspa Hidasari; Wiwik Yunitaningrum; Muhammad Fachrurrozi Bafadal (Universitas PGRI Palembang, 2023)
The era of the industrial revolution 4.0 provides changes and affects various aspects of life. The development of media and technology in the midst of social life is increasingly rapid, resulting in increasingly difficult control over them. Therefore, society needs alternatives in order to balance and avoid the negative effects of media and technology development. Media and technology literacy is the right concept in overcoming the rapid development of media and technology. Media literacy and technology play a role in preparing the community side by side and the impact of media and technology developments. This study aims to determine the media and technological literacy skills of students of the Physical Education Study Program, Faculty of Teacher Training and Education, Tanjungpura University and to determine whether gender and student level factors affect media and technology literacy. The method used in this study is a survey method with data collection tools in the form of questionnaires and data analysis using descriptive-comparative analysis. The population in this study were all 100 students of Physical Education, Tanjungpura University and the sample of this study was 100 students who were taken using a probability sampling technique , namely total sampling. The results of the study show that media and technology literacy is at a moderate level (medium). In this study, it is known that there is no significant difference in media literacy and technology based on the level of students. Meanwhile, based on gender, there is a significant difference in technological literacy but there is no significant difference in media literacy, where the technological literacy level of male students is higher than the female group.